Egy régió kettészakítása : a Bánság kérdése a versailles-i békekonferencián - Gulyás, László (Közép-Európai Közlemények, 2012)
At the end of the 19th – at the beginning of the 20th century economic regions have started to form in Hungary. In case of an undisturbed development these could have become regions similar to the Western European ones. There is a scientific debate on the number and size of these regions, experts speak about 6–10 regions. One of these regions is the Bánság – with Temesvár as its center – that was divided into 3 parts in 1918–20. Most of it went to Romania and Serbia, Hungary could keep only a small part. The last word about the division of the Bánság was said at the peace conference in Versailles. In our paper we analyze the political, economic, ethnic and other reasoning used by the Romanian and Serbian delegation at the peace conference in order to get the Bánság.